Constructing Soluble Anthracene‐Based Blue Emitters Free of Electrically Inert Alkyl Chains for Efficient Evaporation‐ and Solution‐Based OLEDs. Issue 3 (8th February 2022) - Noda, Taito; Sasabe, Hisahiro; Owada, Tsukasa; Sugiyama, Ryo; Arai, Ayato; Kumada, Kengo; Tsuneyama, Hisaki; Saito, Yu; Kido, Junji
Abstract: Anthracene derivatives are one of the most promising blue emitters employed in organic light‐emitting devices (OLEDs) because of their electrochemical and thermal stabilities. However, their high crystallinity owing to their large π‐planar structures severely impedes the progress in the development of solution‐based systems. In this work, we developed two types of highly soluble multifunctional anthracene derivatives terminated with ortho‐biphenyl and triphenylamine moieties and showed high solubility in general organic solvents such as toluene, tetrahydrofuran, and cyclohexanone at high concentrations (>10 mg mL −1 ), and showed blue emission with a peak wavelength of ∼465 nm and a high photoluminescence quantum yield that ranges up to 81 %. Notably, these emitters are suitable for fabricating both evaporation‐ and solution‐based systems. The evaporation‐based system OLED achieved a high external quantum efficiency (EQE) of 5.4 %. While the solution‐processed system realized 4.8 %, exhibiting the best performance among the anthracene‐based solution‐processed OLEDs so far. Abstract : Two types of anthracene derivatives terminated with ortho‐biphenyl and triphenylamine have been developed. These emitters exhibit high solubility in ordinary organic solvents, high photoluminescent quantum yields of ∼81 %, and are suitable for fabricating both evaporation‐ and solution‐based organic light‐emitting devices with a high external quantum efficiency up to 5.4 %.